2007
DOI: 10.1523/jneurosci.4441-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Plasticity and Enhanced Remyelination in the Maternal CNS

Abstract: Myelination, the process in which oligodendrocytes coat CNS axons with a myelin sheath, represents an important but poorly understood form of neural plasticity that may be sexually dimorphic in the adult CNS. Remission of multiple sclerosis during pregnancy led us to hypothesize that remyelination is enhanced in the maternal brain. Here we report an increase in the generation of myelin-forming oligodendrocytes and in the number of myelinated axons in the maternal murine CNS. Remarkably, pregnant mice have an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
175
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 222 publications
(195 citation statements)
references
References 74 publications
18
175
1
1
Order By: Relevance
“…Moreover, PRL has been shown to regulate oligodendrocyte precursor proliferation and mimic the regenerative effects of pregnancy. PRL's striking ability to repair demyelination identifies it as a potential therapeutic agent in multiple sclerosis (48). There could be some potential side effects of higher levels of PRL.…”
Section: Figurementioning
confidence: 99%
“…Moreover, PRL has been shown to regulate oligodendrocyte precursor proliferation and mimic the regenerative effects of pregnancy. PRL's striking ability to repair demyelination identifies it as a potential therapeutic agent in multiple sclerosis (48). There could be some potential side effects of higher levels of PRL.…”
Section: Figurementioning
confidence: 99%
“…In the MS field, PRL has gained renewed interest in recent years, because two studies showed that exclusive breastfeeding (a hyperprolactinemic physiologic condition) reduces the risk for postpartum relapses (35,36), albeit other articles reported discordant results (5,37,38). Further, another article has demonstrated that PRL mediates proliferation of oligodendrocyte progenitor cells during pregnancy and promotes myelin repair in a spontaneously remyelinating model of chemical (lysolecithin)-induced focal demyelination, suggesting PRL as a potential therapeutic agent for MS (39). By studying EAE, an immune-mediated model of demyelination, in PRLR-and PRL-deficient mice, we had the possibility to evaluate the net effect of PRL on disease development between the potential immune-stimulating (detrimental) and myelinogenic (beneficial) properties of this hormone.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition to its primary roles in mammary gland development, as well as the initiation and maintenance of lactation, PRL is believed to be involved in a number of physiological roles, including immune system modulation, cell proliferation and neuroregeneration. [8][9][10][11][12] For example, PRL possesses both pro-and anti-inflammatory properties. High levels of circulating PRL can enhance Th1 cellular activity and antigen-specific T-lymphocyte function in mice.…”
Section: Introductionmentioning
confidence: 99%